Peningkatan Kemampuan Pedagogi Mahasiswa Melalui Model Lesson Study pada Mata Kuliah Microteaching - Dahlan, Rosmidah Rezki; Pellu, Mitha Rahmawati; Kasmawati; Koto, Saifuddin (Academy of Education Journal, 2024)
The purpose of this research is to improve students pedagogical skills through a lesson study model in microteaching courses. The type of research conducted is descriptive research with a qualitative approach. The subjects of the study were 6 students from the Mathematics Education, Biology Education, English Education and Indonesian Education Study Programs at the Faculty of Teacher Training and Education, Iqra Buru University. Data collection uses observation sheets on the lesson plans made and the learning implementation process. The results of the research obtained are: 1) in preparing the learning implementation plan), from the 7 aspects that were assessed, namely: (1) the completeness of the identity of the RPP is obtained from 65% to 85%; (2) the formulation of learning objectives was obtained from 67.8% to 90%; (3) The description of the subject matter was obtained from 65% to 85%; (4) learning methods, strategies and media were obtained by 58%; to 92.6%; (5) the learning plan was obtained by 66.6%, to 84.3%; (6) The assessment was obtained by 70%, to 90%; and (7) learning resources were obtained by 75%, to 88.5. 2) Implementation (Do) with the application of lesson study there was a very good increase where from 3 aspects that were assessed to obtain ideals, namely (1) Introduction, 68.7% to 88% of categories; (2) Core, 61.6%, to 85%; and (3) 65% cover to 95. In conclusion, the application of the lesson study model in microteaching courses can improve students' pedagogical teaching skills.